Study guide. - Weygandt, Jerry J. (John Wiley & Sons, 2001)
Stockholders' Equity: Contributed. Stockholders' Equity: Retained earnings. Dilutive securities and Earnings Per share. Investments. Revenue recognition. Accounting for income taxes. Accounting for pensions and postretirement benefits. Accounting for leases. Accounting changes and erroe analysis. Statement of cash flows. Full disclosure in financial reporting.